Meta-Analysis the Effect of Hydrotherapy on the Elevation of Motoric Functional Ability in Post Stroke Patients - Wibisono, Lilik Sigit; Prasetya, Hanung; Murti, Bhisma (Indonesian Journal of Medicine, 2022)
Background: Stroke is the third leading cause of death in the world after heart and cancer and the disease that causes serious and permanent disability is the first in the world. Hydrotherapy in stroke plays a role in developing, maintaining, and restoring movement and function with motor training based on an understanding of the pathophysiology, neurophysiology, kinematics and kinetics of normal motion. The purpose of this study was to analyze the effect of hydrotherapy on improving motor functional ability in post-stroke patients.Subjects and Method: This study was a meta-analysis with the following PICO, population: stroke patients. Intervention: administration of hydrotherapy. Comparison: Standard therapy. Result: motor functional improvement. The articles used in this study were obtained from three databases, namely Google Scholar, Pubmed, and Science Direct. Keywords to search for articles “hydrotherapy” OR “Aquatic therapy” AND “functional enhancement” AND “post stroke”. The articles included are full-text English with a randomized control trial study design from 2002 to 2022. Article selection was carried out using PRISMA flow diagrams. Articles were analyzed using the Review Manager 5.3 application.Results: A meta-analysis of 9 studies from China, Korea, Italy, Spain and Brazil concluded that hydrotherapy has an effect on post-stroke functional improvement. Post-stroke patients who received hydrotherapy intervention had motor functional ability 0.68 units higher than those who did not receive hydrotherapy. The difference was significant (SMD= 0.68; 95% CI = 0.44 to 0.91; p=0.001).Conclusion: Hydrotherapy improves motor functional ability of post-stroke patients.Keywords: Hydrotherapy, functional enhancement, post strokeCorrespondence: Lilik Sigit Wibisono. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Mobile: 087779982774. Email: lilik21_1990@student.uns.ac.id.Indonesian Journal of Medicine (2022), 07(01): 73-81https://doi.org/10.26911/theijmed.2022.07.01.08